The European Commission's Scoreboard of Macroeconomic Imbalances: The impact of preferences on an early warning system - Tobias Knedlik (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
The European Commission s Scoreboard of Macroeconomic Imbalances is a rare case of a publicly released early warning system. It allows the preferences of the politicians involved to be analysed with regard to the two potential errors of an early warning system missing a crisis and issuing a false alarm. Such an analysis is done for the first time in this article for early warning systems in general by using a standard signals approach, including a preference-based optimisation approach, to set thresholds. It is shown that, in general, the thresholds of the Commission s Scoreboard are set low (resulting in more alarm signals), as compared to a neutral stand.
Keywords: G01; F47; F53; 330